2009
DOI: 10.3797/scipharm.0907-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Glucose Entrapment and Alpha-Glucosidase Inhibition of Mucilaginous Substances from Selected Thai Medicinal Plants

Abstract: As a continuous searching for anti-diabetic(type II) substances, seven mucilage polysaccharides from selected plants were studied as follow: aerial parts of Basella alba Linn., fruits of Hibiscus esculentus Linn., leaves of Litsea glutinosa (Lour.) C.B. Robinson, seeds of Ocimum canum Sims., seeds of Plantago ovata Forssk., fruits of Scaphium scaphigerum G. Don. and seeds of Trigonella foenum-graecum Linn. The bioactive properties for entrapping glucose, inhibiting enzyme alpha-glucosidase and free radical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Dawkins and Nnanna [7] also reported a high percentage of glucose (98.4%) in the gum from oat seed. As reported by Palanuvej et al [8], galactose and glucose were the main monosaccharide in the chemical composition of glucomannan from Litsea glutinosa leaves, Hibiscus esculentus and Scaphium scaphigerum fruits, Ocimum canum , Plantago ovata and Trigonella foenum-graecum seeds. As shown in Table 1, the percentage of glucose and galactose of durian seed gum was higher than that of Yanang gum [9], locust bean gum [10], malva nut gum [11], and Prosopis seed gum [12].…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Dawkins and Nnanna [7] also reported a high percentage of glucose (98.4%) in the gum from oat seed. As reported by Palanuvej et al [8], galactose and glucose were the main monosaccharide in the chemical composition of glucomannan from Litsea glutinosa leaves, Hibiscus esculentus and Scaphium scaphigerum fruits, Ocimum canum , Plantago ovata and Trigonella foenum-graecum seeds. As shown in Table 1, the percentage of glucose and galactose of durian seed gum was higher than that of Yanang gum [9], locust bean gum [10], malva nut gum [11], and Prosopis seed gum [12].…”
Section: Resultsmentioning
confidence: 52%
“…Palanuvej et al [8] also reported the presence of minor content of xylose and arabinose in the chemical composition of glucomannan from Litsea glutinosa leaves, Hibiscus esculentus and Scaphium scaphigerum fruits. As stated by previous researchers [13], arabinose is a pentose monosaccharide which contributes to the molecular structure of various plant gums.…”
Section: Resultsmentioning
confidence: 99%
“…Acute oral toxicity study was performed as per OECD-423 guidelines (acute toxic class method), albino rats of either sex selected by random sampling were used for acute toxicity study [13] . The animals were kept fasting for overnight and provided only with water, after which the extracts were administered orally at 5mg/kg body weight by gastric incubations and observed for 14 days.…”
Section: Acute Toxicity Studiesmentioning
confidence: 99%
“…[10] Basella alba has been used for the treatment of Anemia in women, coughs, cold (leaf with stem), cold related infections. [13] Maceration is taken orally for infertility, pelvic inflammatory disease, epididymytis, threatened abortion, spurious labour. [14] Leaves are used in constipation, poultice for sores, urticaria and gonorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The mucilage present in B. alba has been credited with hypoglycaemic activity. [11] It also possess CNS depressant activity, gastro protective activity,[1213] anti-inflammatory activity,[1415] membrane stabilization property in human blood cell membrane,[16] antibacterial activity,[17] wound healing and anti-ulcer activity. [1819] B. alba is consumed in food preparations in southern India.…”
Section: Introductionmentioning
confidence: 99%